PERLINDUNGAN HUKUM TERHADAP PEMEGANG SERTIPIKAT HAK MILIK ATAS TANAH YANG MENGALAMI SENGKETA - Tista, Adwin (Lambung Mangkurat Law Journal, 2019)
The purpose of this study is to determine legal protection of the land rights certificate holders who have ownership disputes and the settlement of disputes over land ownership rights by promoting the principle of legal protection. This research is a kind of normative law. Object of research is the ownership certificates of land ownership disputes are experiencing.The results of the study, First: The legal protection against the certificate holder the right to land ownership disputes are experiencing can be done if: Certificate of land rights legally issued on behalf of the person or legal entity; Land diperloleh in good faith; ground controlled and maintained substantially; Within 5 years from the issuance of certificates of land rights, no one filed a written objection to the certificate holder and the head office of district/city land local or not filed a lawsuit to court over control of the land or the certificate issuance process. Second: Settlement of disputes over land ownership rights are: Settlement of disputes over land ownership rights with mengedepan- the principle of legal protection through the agency BPN; or through the courts, either in the Court of Common-related issues of land ownership rights or in the Court of the State Administration of related problems have grappled in procedures for issuance of certificates of land rights, dispute resolution through ADR, Settlement of disputes by based on the decision of the judge who put forward the principle of legal protection